EVALUASI KINERJA BUS TRANSJAKARTA KORIDOR 3 (KALIDERES â€“ PASAR BARU) (Jurnal Planesa (Planologi), 2016)
Basically the public transport that the user wants is a reliable, fast, convenient, and secure public transport. Where the performance of public transport, and can be seen based on the services provided, such as; waiting time for passengers, travel time, bus capacity, number of bus fleet needs, etc. TransJakarta bus is one of public transportation which is a solution to overcome transportation problem in DKI Jakarta, but at certain hours the number of available buses is not sufficient to transport passengers, and impact on new problems, such as the length of time waiting for bus, accumulation of passengers, and the lack of number of bus armada. The purpose of this study is to know the capacity of TransJakarta bus in corridor 3 Kalideres - Pasa Baru, whether it is in accordance with the number of passengers. Is the number of TransJakarta bus unit in corridor 3 Kalidere - Pasar Baru, TransJakarta bus number can accommodate passenger capacity in corridor 3 Kalideres - Pasar Baru. And how does the user respond to, TransJakarta bus performance in corridor 3 Kalideres - Pasar Baru. This research uses simple random sampling method, Load factor, passenger calculation, Headway distance, Travel time, and Total Fleet Requirement. Factor load (load factor) from the analysis results that the morning load factor at 06.00-10.00 is 0.96, noon at 13.00-15.00 of 0.84 and afternoon at 16.00-19.00 with 1.41. For the number of buses available, 80 additional units of buses are required to meet passenger needs, the user's response to the performance of the TransJakarta bus, has been stated well and accordingly.Â Keywords: public transport, Transjakarta Bus, total fleet